2014
DOI: 10.1038/onc.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution chromatin immunoprecipitation (ChIP) sequencing reveals novel binding targets and prognostic role for SOX11 in mantle cell lymphoma

Abstract: SOX11 (Sex determining region Y-box 11) expression is specific for MCL as compared to other Non-Hodgkin's lymphomas. However, the function and direct binding targets of SOX11 in MCL are largely unknown. We used high-resolution ChIP-Seq to identify the direct target genes of SOX11 in a genome-wide, unbiased manner and elucidate its functional significance. Pathway analysis identified WNT, PKA and TGF-beta signaling pathways as significantly enriched by SOX11 target genes. qCHIP and promoter reporter assays conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 54 publications
0
45
1
Order By: Relevance
“…The conclusion that BCR signaling plays a pathogenic role in MCL is consistent with emerging data on the role of SOX11 in this lymphoma. [35][36][37] The transcription factor SOX11 enforces expression of the lineage master regulator PAX5. 1,37 PAX5 maintains the B-cell program and prevents terminal plasma-cell differentiation, thereby preserving the cellular responsiveness to antigen induced activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion that BCR signaling plays a pathogenic role in MCL is consistent with emerging data on the role of SOX11 in this lymphoma. [35][36][37] The transcription factor SOX11 enforces expression of the lineage master regulator PAX5. 1,37 PAX5 maintains the B-cell program and prevents terminal plasma-cell differentiation, thereby preserving the cellular responsiveness to antigen induced activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, other studies report reduced cell proliferation upon SOX11 expression in MCL cells. 10,11 The non-malignant, IL-3 dependent pro-B cell line Ba/F3, which does not express immunoglobulins, 12 has previously been used for evaluating the transformation capability of potential oncogenes. 13 Here we used the Ba/F3 cell line to investigate the functional and transcriptional changes resulting from induced Sox11 expression.…”
mentioning
confidence: 99%
“…73 Further studies using ChIP-seq has pin-pointed WNT signaling as a potential important pathway down-stream of SOX11. 49 In a separate study by Vegliante et al, they suggest that SOX11 blocks terminal B-cell differentiation in aggressive MCL through direct positive regulation of PAX5. 74 It is known that SOX genes are promiscuous in their DNA binding capacity and thus, it is not surprising that several pathways may be affected -but it remains to be determined which ones are of most biological value for MCL pathogenesis (see schematic illustration in Figure 1C).…”
Section: The Molecular Function Of Sox11 In MCLmentioning
confidence: 99%
“…46,47 This is in contrary to studies presented by Nygren et al and Kuo et al, which concluded that most of their indolent MCL patients were SOX11 positive. 49,57 Recently, two independent studies associated increased SOX11 expression with improved overall survival in patients treated with either the Nordic protocol 22 ( Figure 1A) or with R-Hyper-CVAD 49 pin-pointing a role of SOX11 as a predictive biomarker for these treatments.…”
Section: Sox11 As a Prognostic Toolmentioning
confidence: 99%
See 1 more Smart Citation